The Implications of Brexit for UK and EU Regional Competitiveness - Mark Thissen; Frank G. van Oort; Philip McCann; Rauel Ortega-Argilés; Trond Husby (Tinbergen Institute, 2019)
Any form of Brexit will impact heterogeneously in terms of sectors and regions on the competitiveness of firms in both the UK and Europe. The ongoing uncertainty about the conditions under which the UK will be leaving the EU, creates difficulties in structurally estimating these impacts. Using uniquely-detailed interregional trade data on goods and services for the EU, we apply a novel methodology that disentangles region-sector sensitivities (elasticities) of firmsâ exteuro™ competitiveness to (non)tariff barriers from the implications of different post-Brexit UK-EU trade scenarios. This enables us to derive the impact of Brexit on the competitiveness of firms along with the degree of uncertainty that surrounds these impacts, independently from the scenarios. Our analysis demonstrates that the adverse international competitiveness shocks on UK firms are much larger than those on the rest of the EU due to the dependency of the UK on the EU via global value chains. The competitiveness shocks mean that within the UK, Brexit is likely to increase both interregional inequalities and also intra-regional inequalities. In contrast interregional inequalities across Europe may actually fall, depending on the nature of the post-Brexit UK-EU trading arrangements.
Keywords: P25; R13; B27; 330; Brexit; competitiveness; impact analysis; international trade; regional economics; IO analysis